PECULIARITIES OF AGE-RELATED QUALITY OF LIFE DYNAMICS OF INFANTS WITH CONSEQUENCES OF PERINATAL CENTRAL NERVOUS SYSTEM LESIONS - V.S. Stupak; V.I. Starodubov; I.V. Vinyarskaya; О.М. Filkina; V.V. Chernikov; N.V. Dolotova ("Paediatrician" Publishers LLC, 2011)
Quality of life is one of the most important parameters of infant vital functions. Its evaluation allows planning rehabilitation of infants with perinatal CNS lesions more precisely on various age levels. The research has been carried in the Center of perinatology Ministry of healthcare Khabarovsk Region. It included 1000 infants. 1000 parents and physicians that were following these infants up were interviewed. Quality of life was evaluated with the use of Russian version of international questionnaire QUALIN (QualitedevieduNourisson). It has been shown that quality of life of infants with CNS lesion consequences is lower than that of healthy infants. Their quality of life was improving with age, though it still remained lower than that of healthy infants. During the 1st year rehabilitation of infants with CNS lesions should be aimed at optimization of their physical and neuropsychic development and family environment, and between 1st and 3rd year of life - at behavior and communication, neuropsychic and physical development and family environment.Key words: quality of life, infants, consequences of perinatal lesions of central neurvous system, QUALIN questionnaire. (Voprosy sovremennoi pediatrii - Current Pediatrics. - 2011; 10 (6): 7-13.)